2017
DOI: 10.1097/olq.0000000000000536
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Transmitted Infections and Associated Risk Factors Among Street-Based and Residence-Based Female Sex Workers in Dhaka, Bangladesh

Abstract: Despite receiving HIV/STI prevention services, bacterial STIs remain prevalent among FSWs suggesting the need for more effective management of STIs. The guidelines for management of STIs need revision in view of the emerging resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 19 publications
0
12
0
6
Order By: Relevance
“…gonorrhoeae was found only in 18.9% of study patients which was much lower than the rates (35.5%)among the sex workers reported by Nessa et al 54 and Rahman et al 55 But the result of present study was much higher than that of a previous study (5.4%) in Bangladesh. 1 In this study, among PCR positive cases, the rate of mixed infections (66.3%) was higher than that of single infection (33.7%). In contrast, Sylverken et al found higher rate of single infection (57.1%) than that of the mixed infections (42.9%).…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…gonorrhoeae was found only in 18.9% of study patients which was much lower than the rates (35.5%)among the sex workers reported by Nessa et al 54 and Rahman et al 55 But the result of present study was much higher than that of a previous study (5.4%) in Bangladesh. 1 In this study, among PCR positive cases, the rate of mixed infections (66.3%) was higher than that of single infection (33.7%). In contrast, Sylverken et al found higher rate of single infection (57.1%) than that of the mixed infections (42.9%).…”
Section: Discussionmentioning
confidence: 46%
“…Correspondence: WHO approaches syndromic management (SM) for the diagnosis of cervicitis and other sexually transmitted infections.But cervicitis in FSWsis mostly asymptomatic or having mild or nonspecific symptoms. 1,38,39,40 So syndromic approach led to many cases untreated or over diagnosed. 41,42 Multiplex PCR are being developed to diagnose multiple organisms in a single clinical samplefrom endocervical specimen in both symptomatic and asymptomatic cervicitis patients which might be helpful to diagnose all the microbes in a single test and also to the clinicians to prescribe appropriate antibiotics for patients according to results.…”
Section: Original Articlementioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, street-based workers live lives more vulnerable to disruption and distraction as studies have shown that they are at higher risk for HIV and sexually transmitted infections, violence, depression, and child-related financial strain. 12,[39][40][41] Outside of our study, there is evidence that the relationship between FSWs and law enforcement is strained. Our finding of an association of nonadherence with arrest is plausible since FSWs with HIV are likely separated from their medication when arrested.…”
Section: Discussionmentioning
confidence: 82%